MENINGKATKAN KEMAMPUAN MENGENAL KONSONAN BILABIAL PADA KATA BENDA DENGAN MENGGUNAKAN MEDIA POWER POINT BAGI ANAK AUTIS - Mariatul, Zulmiyetri, Irdamurni (Jurnal Penelitian Pendidikan Khusus, 2013)
The research problem is motivated by an autistic child (x) in the class 1C1 SLB Lintau Buo, where the child always eliminate consonants b, m, p every word read. The facts show that the child has problems in recognizing consonants b, m, p. Therefore, researchers choose power point media to reduce omission b, m, p in children. The study was a single subject design research with ABA. Results of data analysis showed that during the study period of 30 days seems to improvements in children's ability of stable baseline only 2 words to increase to 24 words after being given intervention. This proves the provision of media power point positive impact in reducing omission b, m, p for autistic class Bhayangkari Linta Buo 1CI SLB. From these results it can be concluded that the provision of power point media can reduce omission on nouns for autistic (x)